Analisis Dampak Lingkungan Pengolahan Limbah Fly Ash dan Bottom Ash dengan Metode Siklus Daur Hidup (Life Cycle Assessment/LCA) di Industri Pembangkit Listrik Tenaga Uap - Intan Dwi Wahyu Setyo Rini; Madah Maria; Eka Masrifatus Anifah; Andika Ade Indra Saputra; Adrian Gunawan; Ahmad Ibnu Arobi (LPPM ITK, 2022)
PLTU Teluk Balikpapan with a 2 x 110 MW capacity generated fly ash and bottom ash as its waste. The waste was treated by backfilling on open land or called a landfill. The landfill was not effective because it required a large area to accommodate the waste. This research aimed to analyze waste treatment's environmental impact and identify the best scenario from three fly ash and bottom ash treatment options. The first scenario was the existing treatment that used landfill, the second was utilization into paving blocks, and the third was utilization into compost. The method in this research used Life Cycle Assessment (LCA) method. The LCA stages referred to ISO 14040 of 2006 which consists of objectives and scope, inventory analysis, impact analysis, and interpretation. The results of the analysis of the contribution of impacts on the environment with Scenario 1 obtained three impacts with the highest value, namely natural land transformation with a value of 15.8 then climate change with a value of 9.5, and particulate matter formation with a value of 6.8. Furthermore, the calculation shows that the best scenario for fly ash and bottom ash waste treatment was scenario 3: processing into compost.